PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INDEX CARD MATCH DISERTAI TUGAS RUMAH TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII SMP PERTIWI 2 PADANG - Busrianti, Sania - (STKIP PGRI Sumbar, 2014)
This research was conducted due to the students low learning achievement in Biology. This could be seen from the students average score in Biology in class VIII of SMP Pertiwi 2 Padang which was below the Minimum Standard Score. This problem was caused by teacher who acted as the center of information, and the students merely listened to and took note on. The materials being explained. The students did not have a chance to ask questions on the materials remaining unclear. This then made the students had low learning activities and motivation. This research was inteded to reveal the effect of using Index Card Match cooperative learning model assisted with homework on the students Biology learning achievement in class VIII of SMP Pertiwi 2 Padang. This was an experimental research which used Randomized Control-Group Posttest Only Design. The population of this research was the students in class VIII of SMP Pertiwi 2 Padang registered in Academic Year 2013/2014. By using purposive sampling technique, class VIII2 was chosen as the experimental group and class VIII3 was as the control group. The data of the reserch was the students learning achievement on cognitive aspect. The data which had been tested its normality and homogenity then was analyzed by using t-test. Based on the result of the posttest, it was figured out the students average school in the experimental class was 80,31 and in the control class was 75,02. The result of t-test showed that the value of tcalculated (1,45) was smaller than ttable (1,67) indicating that the hypothesis was rejected. Thus, the use of Index Card Match cooperative learning model assisted with homework could not improve the students learning achievement in Biology in class VIII of SMP Pertiwi 2 Padang.